The Gateway to Computer Science Excellence
First time here? Checkout the FAQ!
x
0 votes
49 views
S->abA

A->baB

B->aA|bb

convert this to left linear grammar
asked ago in Theory of Computation by Active (4k points) | 49 views

2 Answers

+1 vote
Best answer
$L = \begin{Bmatrix} abbabb, abbaababb, abbaabaababb,.............. \end{Bmatrix}$

 

$L = \begin{Bmatrix} abba(aba)^*bb \end{Bmatrix}$

 

$Left \ Linear \ Grammer :$

 

$S\rightarrow Abb$

$A\rightarrow Aaba/C$

$C\rightarrow abba$
answered ago by Loyal (8.1k points)
selected ago by
+1 vote
The left linear grammar corresponding to the given grammar is given below

S ---> Abb

A ---> Aaba | abba
answered ago by Loyal (5.6k points)


Quick search syntax
tags tag:apple
author user:martin
title title:apple
content content:apple
exclude -tag:apple
force match +apple
views views:100
score score:10
answers answers:2
is accepted isaccepted:true
is closed isclosed:true

35,485 questions
42,741 answers
121,445 comments
42,135 users